2010
DOI: 10.20396/etd.v8i1.1116
|View full text |Cite
|
Sign up to set email alerts
|

Concepções de alunos do curso de psicopedagogia a respeito das dificuldades de aprendizagem

Abstract: Neste trabalho apresentamos um recorte de uma pesquisa que investiga as idéias e concepções de psicopedagogos e pedagogos em relação às dificuldades de aprendizagem. Analisamos aqui as respostas de estudantes dos cursos de Psicopedagogia de instituições particulares do interior do estado de São Paulo e Minas Gerais. Foram selecionados aleatoriamente estudantes que estavam no início, no meio e no final do curso de especialização, totalizando 52 sujeitos participantes da pesquisa. Todos os sujeitos responderam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A study 20 addressed the knowledge of 52 teachers who were taking a specialization course in educational psychology. When asked "What is a learning disability?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study 20 addressed the knowledge of 52 teachers who were taking a specialization course in educational psychology. When asked "What is a learning disability?"…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [19][20][21] that focused on teachers' knowledge about school difficulties and learning disorders have shown that in relation to the causes that justify the diagnosis of disorder of reading and writing, most pointed to intrinsic causes (physiological, biological) as causes for the reading and writing disorder, while a minority pointed to extrinsic causes such as the school environment, teaching method, and family environment.…”
Section: Introductionmentioning
confidence: 99%